Mediation, moderation, and context: Understanding complex relations among cognition, affect, and health behaviour. Issue 1 (2nd January 2018) - Kiviniemi, Marc T.; Ellis, Erin M.; Hall, Marissa G.; Moss, Jennifer L.; Lillie, Sarah E.; Brewer, Noel T.; Klein, William M.P.
Abstract : Objective: Researchers have historically treated cognition and affect as separate constructs in motivating health behaviour. We present a framework and empirical evidence for complex relations between cognition and affect in predicting health behaviour. Main Outcome, Design and Results: First, affect and cognition can mediate each other's relation to health behaviour. Second, affect and cognition can moderate the other's impact. Third, context can change the interplay of affect and cognition. Fourth, affect and cognition may be indelibly fused in some psychological constructs (e.g. worry, anticipated regret and reactance). These four propositions in our framework are not mutually exclusive. Conclusion: Examination of the types of complex relations described here can benefit theory development, empirical testing of theories and intervention design. Doing so will advance the understanding of mechanisms involved in regulation of health behaviours and the effectiveness of interventions to change health behaviours.